'Female genital mutilation' in Europe: Public discourse versus empirical evidence. (December 2017) - Johnsdotter, Sara; Mestre i Mestre, Ruth M.
Highlights: There is a discrepancy between public discourse and empirical evidence regarding 'female genital mutilation' in Europe. Framing FGM as a widespread social problem in Europe creates myths about activities among immigrant communities. An analysis of court cases in Europe shows that the typical European case is FGM performed in Africa. Public discourse regarding FGM needs to be challenged in multicultural democracies under the rule of law.